Feasibility and related outcome of intraluminal pulmonary artery banding - Sandrio, Stany; Purbojo, Ariawan; Arndt, Florian; Toka, Okan; Glöckler, Martin; Dittrich, Sven; Cesnjevar, Robert; Rueffer, Andre (European Journal of Cardio-Thoracic Surgery, 2015)
This retrospective study evaluated the feasibility and related outcome of intraluminal pulmonary artery banding (I-PAB).Thirty-two children underwent I-PAB between July 2006 and April 2014. The median age and weight were 60 days (range: 5 days to 4.2 years) and 3.7 kg (range: 2.6-13.0 kg), respectively. Cardiac diagnoses included single ventricle morphology (n = 11), complex ventricular septal defects (n = 11), balanced atrioventricular septal defects (n = 3), congenitally corrected transposition of the great arteries (n = 2) and aortic arch hypoplasia with ventricular septal defects (n = 5). On cardiopulmonary bypass (CPB), 2 I-PAB modifications with either 1 (n = 24) or 2 ('hour-glass-technique', n = 8) fenestrated pericardial patches were performed.The median fenestration size was 5 mm (range: 4-6.5 mm). In 18 patients I-PAB was a solitary procedure; in 3 of them the decision was made intraoperatively. There was no hospital mortality. The median interval to debanding was 189 days (range: 112 days to 2.6 years). During this period, we observed a significant increase in the pressure gradient over I-PAB (P < 0.01), whereas arterial saturations remained stable. Four patients received balloon dilatation of I-PAB to prolong the palliation period. No patient experienced band occlusion, pulmonary hypertension related to I-PAB, coronary or pulmonary valve impairment. Debanding was performed in 27 patients and one of them required pulmonary patch arterioplasty due to I-PAB-associated pulmonary trunk distortion. Three patients are still awaiting further surgery. There were 2 late deaths prior to, and 3 after debanding, all not related to I-PAB.I-PAB with an exactly defined internal orifice is feasible and effective. Although arterial saturations seem to remain stable, balloon dilatation of I-PAB can be performed safely and efficiently in order to prolong the palliation period. The rate of I-PAB-related complications is low, which might improve the long-term patient outcome. Therefore, despite requiring CPB, I-PAB is our institutional preference for children who require pulmonary artery banding.
EVALuna2:25111